Koguryo and Altaic : on the role of Koguryo and other Old Korean idioms in the Altaic etymology - Václav Blažek; Michal Schwarz (Linguistica Brunensia, 2013)
In the contribution all seriously interpreted lexemes of the language of one of Old Korean kingdoms, Koguryo, are presented. Although the main source of these interpretations is a very careful philologist Ch. I. Beckwith known for his negative position concerning the genetic model of the Altaic theory, the collected material compared with EDAL and other Altaic idioms (included Khitan and Jurchen) supports the Altaic affiliation of both Old Koguryo and Japanese. Nevertheless the analysis of this article supports the Beckwith's supposition that Koguryo is the closest relative of Ryukyu-Japanese.